2003
DOI: 10.4049/jimmunol.170.2.1010
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine Type I IFN and Contact with Endothelium Promote the Presentation of Influenza A Virus by Monocyte-Derived APC

Abstract: Purified monocytes infected with influenza A virus do not become mature dendritic cells (DCs) and they present viral peptides poorly to autologous memory T cells. In this study, we investigated whether influenza A-infected monocytes matured to DCs with a high capacity to stimulate T cells when they were infected with influenza A virus in a model tissue setting wherein they were cocultured with endothelium grown on a type I collagen matrix. Intercellular interactions with endothelium strongly promoted the Ag-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 40 publications
(47 reference statements)
1
30
0
Order By: Relevance
“…Thus, the inflammatory milieu induced by M. tuberculosis might be enriched with IFN-␣ that, in turn, could favor the differentiation of recruited monocytes into DCs (40). The autocrine secretion of IFN-␣ has also been suggested to be a modulator of monocyte differentiation in a model tissue setting in which monocytes were cocultured with endothelium grown on a type I collagen matrix (35). In this regard, in vivo experiments clearly indicated that M. tuberculosis strains with the ability to induce IFN-␣ displayed increased virulence and a capacity to induce disease (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the inflammatory milieu induced by M. tuberculosis might be enriched with IFN-␣ that, in turn, could favor the differentiation of recruited monocytes into DCs (40). The autocrine secretion of IFN-␣ has also been suggested to be a modulator of monocyte differentiation in a model tissue setting in which monocytes were cocultured with endothelium grown on a type I collagen matrix (35). In this regard, in vivo experiments clearly indicated that M. tuberculosis strains with the ability to induce IFN-␣ displayed increased virulence and a capacity to induce disease (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…However, we have found that this is stimulus dependent and that, when appropriately stimulated, nonplasmacytoid mouse DC also produce high amounts of IFN␣. 5 Similarly, nonplasmacytoid human monocyte-derived DC produce type I IFN in response to infection with influenza (43,44).…”
Section: Endritic Cells (Dc)mentioning
confidence: 99%
“…In patients with lupus, there is an association between disease activity and type I IFN levels in the peripheral blood [24][25][26][27]. Not all lupus patients have measurably increased levels of type 1 IFN, but they may have increased type 1 IFN-responsive gene expression "signatures" in blood mononuclear cells [16,18]. This suggests that these cells have been exposed to high levels of type 1 IFN elsewhere (e.g., in the tissues).…”
Section: Clinical Discussionmentioning
confidence: 99%
“…In both disorders the lymph node pathology can show histiocytic necrotizing lymphadenitis, and in both, the plasmacytoid histiocyte or PDC plays a role. In the lymph node, PDCs are localized to the "T zone," which is centered around the high endothelial venules [15], where they also present antigen [16]. The pathology in KFD often centers around T zone of the lymph node [17], although in this case, the lymph node architecture was not preserved and the T zone was not clearly seen.…”
Section: Clinical Discussionmentioning
confidence: 99%